Clinical Utility of Rapid Exome Sequencing Combined With Mitochondrial DNA Sequencing in Critically Ill Pediatric Patients With Suspected Genetic Disorders - Ouyang, Xuejun; Zhang, Yu; Zhang, Lijuan; Luo, Jixuan; Zhang, Ting; Hu, Hui; Liu, Lin; Zhong, Lieqiang; Zeng, Shaoying; Xu, Pingyi; Bai, Zhenjiang; Wong, Lee-Jun; et al. (Frontiers in Genetics, 2021)
Genetic disorders are a frequent cause of hospitalization, morbidity and mortality in pediatric patients, especially in the neonatal or pediatric intensive care unit (NICU/PICU). In recent years, rapid genome-wide sequencing (exome or whole genome sequencing) has been applied in the NICU/PICU. However, mtDNA sequencing is not routinely available in rapid genetic diagnosis programs, which may fail to diagnose mtDNA mutation-associated diseases. Herein, we explored the clinical utility of rapid exome sequencing combined with mtDNA sequencing in critically ill pediatric patients with suspected genetic disorders. Rapid clinical exome sequencing (CES) was performed as a first-tier test in 40 critically ill pediatric patients (aged from 6 days to 15 years) with suspected genetic conditions. Blood samples were also collected from the parents for trio analysis. Twenty-six patients presented with neuromuscular and/or other systemic abnormalities, suggestive of suspected mitochondrial diseases or the necessity for a differential diagnosis of other diseases, underwent rapid mtDNA sequencing concurrently. A diagnosis was made in eighteen patients (45.0%, 18/40); three cases with de novo autosomal dominant variants, ten cases with homozygous or compound heterozygous variants, three cases with hemizygous variants inherited from mother, three cases with heterozygous variants inherited from either parent, and one case with a mtDNA mutation. The 18 patients were diagnosed with metabolic (n=7), immunodeficiency (n=4), cardiovascular (n=2), neuromuscular (n=2) disorders, and others. Genetic testing reports were generated with a median time of 5 days (range, 3 to 9 days).Thirteen patients that were diagnosed had an available medical treatment and resulted in a positive outcome. We propose that rapid exome sequencing combined with mitochondrial DNA sequencing should be available to patients with suspected mitochondrial diseases or undefined clinical features necessary for making a differential diagnosis of other diseases.